Results Of Treatment With Methotrexate Under Local Guide Ultrasound In Patients With Pregnancy Complicated Ectopic Surgical Indication In The Gynecology Service Of The National Maternal Perinatal Institute - Garnique-Moncada, Marco (2019)
Objective. Evaluate the results of a series of consecutive cases of ectopic pregnancies complicated with surgical indication according to our current management guidelines of ectopic pregnancy in the National Maternal Perinatal Institute (INMP) who were managed with local injection of methotrexate (MTX) guided by transvaginal ultrasound, in addition to its application intramuscularly. Materials and methods. It is a prospective, longitudinal intervention study. Nine patients with diagnosis of ectopic pregnancy (EP) uncomplicated with surgical indication in the hospital department of gynecology at INMP, who were offered treatment by administering local MTX under ultrasound and intramuscular guide and track were studied both ultrasound and serum chorionic gonadotropin beta fraction (hCG beta) until complete resolution of ectopic pregnancy. Absolute and relative frequencies for categorical variables and measures of central tendency and dispersion for continuous variables were estimated.